The Effect Thyroxine Hormone with Different Doses and Age of Larvae on Growth and Survival Rate of Snakehead (Channa striata) Larvae - Hanifa, Hanifa; Aryani, Netti; Sukendi, Sukendi (Jurnal Kelautan dan Perikanan Indonesia, 2022)
This research was conducted on November - December 2021, at Fish Hatchery and Breeding Laboratory of Fishery and Marine Faculty of Riau University. The research aim is to determine the effect of thyroxin hormone with doses and different age on growth and survival rate of snakehead larvae. The method used was Completely Randomized Design Factorial. The first factor was the different doses with 4 levels, namely 0 mg/L (D0), 0,3 mg/L (D1), 0,5 mg/L (D2) and 0,7 mg/L (D3). The second factor is larvae age with 3 levels, namely 3 days (U3), 5 days (U5) and 7 days (U7). Larvae was rearing for 40 days in an aquarium with a density of 2 fish/L. The findings showed that thyroxin hormone with different doses and larvae age affected the growth of absolute weight and length, specific growth rate, and also survival rate of snakehead larvae. The treatment of doses 0,7 mg/L and 7 days of larvae age (D3U7) showed the highest growth, namely absolute weight 3.32 g, absolute length 6,19 cm, specific growth rate of 17.53%/day, and survival rate of 90%. The parameter of water quality during the research was 26,9-28.9C, pH 6.7-7.6, dissolved oxygen 5-7.2 mg/L, and ammonia 0.0024-0.0035 mg/L.Keywords: Thyroxine Doses, Different Age, Channa striata, Growth and Survival Rate